2020
DOI: 10.1152/japplphysiol.00609.2020
|View full text |Cite
|
Sign up to set email alerts
|

In vivo supraspinatus muscle contractility and architecture in rabbit

Abstract: The rotator cuff (RC) muscles are crucial in moving and stabilizing the glenohumeral joint, and tears can be functionally devastating. Chronic fatty and fibrotic muscle changes, which are non-responsive to surgical tendon repair, are a focus of contemporary research. The rabbit model recapitulates key biological features of human RC tears, but function and physiology are poorly characterized-limited force and stress data are inconsistent with literature norms in other mammalian species. Here, we present an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The rabbit model is an advantageous system to use to study this question due to similar morphological changes such as increased fat, fibrosis, and degeneration (Rubino et al, 2007;Farshad et al, 2012;Valencia et al, 2018;Hyman et al, 2020Hyman et al, , 2021Vargas-Vila et al, 2021) to what is observed in the supraspinatus (SSP) in humans (Gibbons et al, 2017(Gibbons et al, , 2018b without the need of a neurectomy as in smaller animal models (Rowshan et al, 2010). The major physiological changes noted in this model include significant decrease in muscle fiber crosssectional area (CSA) at 4 and 16 weeks, degeneration of muscle fibers with a ∼25% muscle mass reduction after 16 weeks, and an increase in collagen and fat between 4 to 16 weeks (Rubino et al, 2007;Farshad et al, 2012;Valencia et al, 2018;Hyman et al, 2020Hyman et al, , 2021Vargas-Vila et al, 2021). Understanding the progression of RC disease before repair may help determine the potential effectiveness of a surgical intervention with or without adjuvant therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…The rabbit model is an advantageous system to use to study this question due to similar morphological changes such as increased fat, fibrosis, and degeneration (Rubino et al, 2007;Farshad et al, 2012;Valencia et al, 2018;Hyman et al, 2020Hyman et al, , 2021Vargas-Vila et al, 2021) to what is observed in the supraspinatus (SSP) in humans (Gibbons et al, 2017(Gibbons et al, , 2018b without the need of a neurectomy as in smaller animal models (Rowshan et al, 2010). The major physiological changes noted in this model include significant decrease in muscle fiber crosssectional area (CSA) at 4 and 16 weeks, degeneration of muscle fibers with a ∼25% muscle mass reduction after 16 weeks, and an increase in collagen and fat between 4 to 16 weeks (Rubino et al, 2007;Farshad et al, 2012;Valencia et al, 2018;Hyman et al, 2020Hyman et al, , 2021Vargas-Vila et al, 2021). Understanding the progression of RC disease before repair may help determine the potential effectiveness of a surgical intervention with or without adjuvant therapeutics.…”
Section: Introductionmentioning
confidence: 99%